(untitled) (International Journal of Current Engineering and Technology, 2014)
In this paper, three different adaptive beamforming algorithms namely Least Mean Square (LMS), Recursive Least Square (RLS) and Conjugate Gradient Method (CGM) for the array antenna systems are studied and their performance is analysed. Literature on adaptive beamforming for array antenna system was focused more on first two methods for the performance analysis. In this work, we focused more on CGM and the compressive comparison is done. All three adaptive beamforming algorithms are developed using MATLAB software. The performance analysis of beam pattern for different array elements are studied, then the convergence speed are compared, Mean Square Error (MSE) and Bit Error Rate (BER) are computed and the results are compared.